Modelling long run comovements in equity markets: A flexible approach - Martins, Luis F.; Gabriel, Vasco J. (Journal of Banking & Finance, 2014)
International equity markets linkages are characterized by nonlinear dependence and asymmetries. We investigate shifts in long run comovements in stock markets by means of an ‘interrupted’ Markov switching cointegration specification. This flexible approach allow us to study to what extent documented changes in global integration are permanent, or whether market linkages are subject to changes. Using an illustrative sample from 1980 to 2012 for USA, UK and Hong Kong stock price indices, we find evidence of interrupted cointegration across these markets between May 1997 and April 2002, which is consistent with the decoupling of stock prices from fundamentals during the dot-com bubble.